Differential cytotoxicity of copper ferrite nanoparticles in different human cells. Issue 10 (25th February 2016) - Ahmad, Javed; Alhadlaq, Hisham A.; Alshamsan, Aws; Siddiqui, Maqsood A.; Saquib, Quaiser; Khan, Shams T.; Wahab, Rizwan; Al‐Khedhairy, Abdulaziz A.; Musarrat, Javed; Akhtar, Mohd Javed; Ahamed, Maqusood
Abstract: Copper ferrite nanoparticles (NPs) have the potential to be applied in biomedical fields such as cell labeling and hyperthermia. However, there is a lack of information concerning the toxicity of copper ferrite NPs. We explored the cytotoxic potential of copper ferrite NPs in human lung (A549) and liver (HepG2) cells. Copper ferrite NPs were crystalline and almost spherically shaped with an average diameter of 35 nm. Copper ferrite NPs induced dose‐dependent cytotoxicity in both types of cells, evident by 3‐(4, 5‐dimethylthiazol‐2‐yl)‐2, 5‐diphenyltetrazoliumbromide and neutral red uptake assays. However, we observed a quite different susceptibility in the two kinds of cells regarding toxicity of copper ferrite NPs. Particularly, A549 cells showed higher susceptibility against copper ferrite NP exposure than those of HepG2 cells. Loss of mitochondrial membrane potential due to copper ferrite NP exposure was observed. The mRNA level as well as activity of caspase‐3 enzyme was higher in cells exposed to copper ferrite NPs. Cellular redox status was disturbed as indicated by induction of reactive oxygen species (oxidant) generation and depletion of the glutathione (antioxidant) level. Moreover, cytotoxicity induced by copper ferrite NPs was efficiently prevented by N ‐acetylcysteine treatment, which suggests that reactive oxygen species generation might be one of the possible mechanisms of cytotoxicity caused by copper ferrite NPs. To the best of our knowledge, this is the first report showing the cytotoxic potential of copper ferrite NPs in human cells. This study warrants further investigation to explore the mechanisms of differential toxicity of copper ferrite NPs in different types of cells. Copyright © 2016 John Wiley & Sons, Ltd. Abstract : Copper ferrite nanoparticles (NPs) have the potential to be applied in biomedical fields such as cell labeling and hyperthermia. However, there is a lack of information concerning the toxicity of copper ferrite NPs. We explored the cytotoxic potential of copper ferrite NPs in human lung (A549) and liver (HepG2) cells. Copper ferrite NPs were crystalline and almost spherically shaped with an average diameter of 35nm. Copper ferrite NPs induced dose‐dependent cytotoxicity in both types of cells, evident by 3‐(4, 5‐dimethylthiazol‐2‐yl)‐2, 5‐diphenyltetrazoliumbromide and neutral red uptake assays.